The Role Of Strategic Direction In Achieving Organizational Commitment )Field Study In Some Hospitals Of The Iraqi Ministry Of Health) - سليطين, سوما; حسين, يحيى (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study aimed to determine the role of the strategic orientation in improving the organizational commitment in Iraqi hospitals, by knowing the influence of the strategic vision, the strategic message, and the strategic goals, and the researcher relied on the descriptive and analytical approach, by describing the phenomena under study through the data collected. And he distributed the questionnaire to 202 personnel working in the hospitals under study, from which 185 questionnaires were retrieved, and then he conducted a field study for the purpose of demonstrating this relationship The most important results of the research were the existence of an important role for strategic direction in its various dimensions (strategic vision, strategic message, strategic goals) in improving organizational commitment, and the most important recommendations were where the hospital’s strategic vision should inspire and inspire enthusiasm for all hospital members. It should also include a message. The hospital has clear information about the group of clients whose needs and desires will be satisfied.